YMCA Building, New York World's Fair, 1940 (Tichnor Brothers, Inc)
The YMCA Building at the World's Fair is located on Hamilton Place, 60 yards from the Statue of George Washington. It is operated by the YMCA of the City of New York as a meeting, resting and eating place for members and friends of every Association in the world. Social rooms, correspondence tables, information service and wash rooms are provided. Cafeteria and table service restaurants serve delicious food at low prices. Both men and women are welcome.